1989
DOI: 10.1086/646062
|View full text |Cite
|
Sign up to set email alerts
|

Legionella pneumophila Grows Adherent to Surfaces in vitro and in situ

Abstract: Legionella pneumophila continues to play a role in both community- and nosocomially-acquired pneumonia. We investigated the ability of L pneumophila to adhere to various types of materials such as those found in the hospital air-cooling and portable water distribution systems. Through the use of a unique sampling apparatus, we were able to regularly acquire planktonic and sessile samples and determine the numbers of bacteria present in both populations, in vitro and in situ. Portions of these apparatuses could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Protozoan hosts are supposed to be crucial for replication of L. pneumophila in aquatic environments (10,12,15,16), although alternative pathways have been suggested (5,18,20,21,27,32). This paper demonstrates that L. pneumophila is able to thrive on heat-killed microbial cells present in biofilms or heattreated water systems.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Protozoan hosts are supposed to be crucial for replication of L. pneumophila in aquatic environments (10,12,15,16), although alternative pathways have been suggested (5,18,20,21,27,32). This paper demonstrates that L. pneumophila is able to thrive on heat-killed microbial cells present in biofilms or heattreated water systems.…”
Section: Discussionmentioning
confidence: 82%
“…On the one hand, it is supposed that L. pneumophila grows within protozoan hosts in aquatic environments and that this interaction is central to the pathogenesis and ecology of L. pneumophila (10,12,15,16). Conversely, a number of studies suggested the protozoon-independent survival and growth of L. pneumophila (18,21,27,32), in which case the bacterium uses biofilm matrices as a shelter and source of nutrients. Although scarce, there is evidence that a number of microorganisms in the proximity of L. pneumophila may favor its growth by excreting extracellular compounds as carbon and energy sources (1,23,29).…”
mentioning
confidence: 99%
“…Once in the system the temperature of the water, < 60°C [11], presence of amoebae [12], turbidity, organic carbon, zinc, copper and algae [13] are all important factors in maintaining growth. Various components of plumbing systems are more readily colonized by legionella than others [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…An extensive study by Kuchta et al (1998) examined interactions between L. pneumophila and Hartmannella vermiformis, and the efficacy of several disinfectants, and strongly suggested the requirement of protozoan organisms as a ' growth factor ' for the cell replication of Legionella. Some investigators (Wright et al, 1989) have carried out in vitro studies of Legionella biofilm formation and have observed biomass accumulation on the substrata in the absence of protozoan cells. These studies have referred to the biomass as ' growth ' ; however, they failed to address whether those Legionella cells were actually dividing in the absence of protozoa or merely surviving, which, in our view, is a more relevant question.…”
Section: Introductionmentioning
confidence: 99%